2023
DOI: 10.5812/gct-131298
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tribulus Terrestris Extract and Endurance Training on Oxidative Stress and Apoptotic Markers in the Kidney Tissue of Rats, Poisoned with Arsenic

Abstract: Background: Inorganic arsenic (As) has destructive effects on the kidneys. The exact mechanism and effects of Tribulus Terrestris (TT) and endurance training (ET) on renal apoptosis and oxidative stress are not quite clear. Objectives: The effects of ET and TT on apoptotic markers and oxidative stress were examined in the kidney tissue of rats, poisoned with As. Methods: In total, 49 rats were randomly allocated to seven groups: (1) control; (2) As (68 mg/L/day for 8 weeks); (3) As + 5 mg/kg TT (As + TT5); (4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Various studies have explored the effectiveness of T. terrestris in safeguarding and rejuvenating liver function when it comes to exposure to toxic substances such as heavy metals found in the environment. It has been discovered that T. terrestris is capable of successfully restoring liver markers that have been negatively impacted by toxic substances such as aluminum, cadmium, mercury, arsenic, CYP, and CCl4 [ 75 , 81 ]. Further analysis of the data revealed that T. terrestris has the potential to shield the liver from a wide range of threats.…”
Section: Phytopharmacological Activities/medicinal Propertiesmentioning
confidence: 99%
“…Various studies have explored the effectiveness of T. terrestris in safeguarding and rejuvenating liver function when it comes to exposure to toxic substances such as heavy metals found in the environment. It has been discovered that T. terrestris is capable of successfully restoring liver markers that have been negatively impacted by toxic substances such as aluminum, cadmium, mercury, arsenic, CYP, and CCl4 [ 75 , 81 ]. Further analysis of the data revealed that T. terrestris has the potential to shield the liver from a wide range of threats.…”
Section: Phytopharmacological Activities/medicinal Propertiesmentioning
confidence: 99%